Evaluation of the effects of a cognitive and neuromotor stimulation program for a group of elderly people with major neurocognitive disorders - Uță, Viorica Mariana; Enache, Rodica Gabriela (Technium Social Sciences Journal, 2022)
The objective of this study is to analyze the neurocognitive decompensation processes in elderly people upon entering care centers and one year after their integration into special programs designed to limit the effects of Alzheimer’s disease and other neurodegenerative diseases. This scientific research will observe the limitation, progression or regression of these types of diseases. Following this study, the major risk factors were identified, group and individual therapies were implemented and the needs of the elderly were determined in order to optimize their neurocognitive functions and increase their quality of life.